Dame Kathleen Kenyon 1906-1978 - Callaway, Joseph A. (The Biblical archaeologist, 1979)
A giant in the land who brought about a revolution in methodology in Palestinian archeology with her introduction of stratigraphic controls and carefully limited excavcations.